2008
DOI: 10.1177/1099800408324251
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Response to Postural Shift in Women with Multiple Chemical Sensitivities

Abstract: Multiple chemical sensitivity (MCS) is a chronic condition prevalent in women; the symptoms are reproducible with repeated low-level chemical exposure. Evidence gathered through clinical observations suggests that women with MCS may be at risk for autonomic nervous system dysfunction as evidenced by abnormal heart rate and pulse pressure responses to exercise. The primary objective of this study was to describe the hemodynamic response to postural shift in 17 women with MCS. Using impedance cardiography, hemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Some patients experience significant discomfort from one or more of these symptoms, as reported in the literature regarding myalgia [ 58 , 59 ], hemodynamic changes [ 60 ], and dizziness. Other evidence showed that some MCS patients could manifest dizziness-related vestibular decay [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some patients experience significant discomfort from one or more of these symptoms, as reported in the literature regarding myalgia [ 58 , 59 ], hemodynamic changes [ 60 ], and dizziness. Other evidence showed that some MCS patients could manifest dizziness-related vestibular decay [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other discovered results with significant association are the symptoms related to item 5, difficulty in concentrating, remembering things or making decisions (OR: 31.25, 13.79–70.80 p = 0.000); this symptom coincides with those reported in the studies by Vuokko et al [ 34 ] and by Del Casale et al [ 1 ]; second, the symptom corresponding to item 3 was found, problems in the heart or chest (tachycardia, arrhythmias, extrasystoles or pain) (OR: 22.49, 8.14–62.13 p = 0.000), although it appeared less frequently in the literature. However, its presence raises the need for further research in this area [ 52 , 53 ]. In women affected by MCS, the symptoms with association correspond to item 7, problems with balance or coordination of movements, numbness or tingling or difficulty in focusing vision (OR: 20.00, 9.13–43.78 p = 0.000); this symptom also was described in studies such as the one conducted by Nogué et al and by Hojo et al [ 10 , 32 ].…”
Section: Discussionmentioning
confidence: 99%